2008
DOI: 10.1093/cvr/cvn048
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-1 prevents hypertension and target organ damage through its interaction with endothelial Tie2 receptor

Abstract: AimsThe endothelium has emerged recently as a therapeutic target in the treatment of hypertension because endothelial dysfunction and subsequent vascular rarefaction cause target organ damage and further elevate blood pressure (BP). It led us to hypothesize that one of the endothelial survival factors, a potent derivative of angiopoietin-1 (cartilage oligomeric matrix protein, COMP-Ang-1), could be a novel class of antihypertensive agents that maintain endothelial integrity and function, thereby preventing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 22 publications
1
21
0
Order By: Relevance
“…81 COMP-Ang-1 reduced microvascular rarefaction and tissue damage in the heart and the kidney and, intriguingly, also prevented the development of hypertension. These effects on systolic blood pressure disappeared when SHRs were pretreated with soluble Tie2 receptor, suggesting that the therapeutic effects of COMPAng-1 were mediated by the endothelium.…”
Section: Pro-angiogenesis Might Reduce the Development Of Hypertensionmentioning
confidence: 90%
See 1 more Smart Citation
“…81 COMP-Ang-1 reduced microvascular rarefaction and tissue damage in the heart and the kidney and, intriguingly, also prevented the development of hypertension. These effects on systolic blood pressure disappeared when SHRs were pretreated with soluble Tie2 receptor, suggesting that the therapeutic effects of COMPAng-1 were mediated by the endothelium.…”
Section: Pro-angiogenesis Might Reduce the Development Of Hypertensionmentioning
confidence: 90%
“…These effects on systolic blood pressure disappeared when SHRs were pretreated with soluble Tie2 receptor, suggesting that the therapeutic effects of COMPAng-1 were mediated by the endothelium. 81 Hypoxia served as the main trigger for angiogenesis, in a recent study, in SHRs. 82 Chronic normobaric hypoxia (10% O 2 ) decreased vascular resistance and, subsequently, systolic blood pressure by 26% already after 3 weeks when compared with normoxia (21% O 2 ).…”
Section: Pro-angiogenesis Might Reduce the Development Of Hypertensionmentioning
confidence: 92%
“…The stabilizing effect of angiopoietin 1 on the vessels was confirmed by the examination of COMP (cartilage oligomeric matrix protein) derived from the intestinal villi. Ang-1 prevents arterial hypertension and organ damage caused by high arterial pressure by the vascular anomalies alternation [29]. The study revealed considerably lower Ang-1 concentration, and higher concentration of Ang-2 in serum of patients with toxic goitre after the surgery, which appears to contradict the stabilizing function of Ang-2.…”
Section: Nss Ss Ssmentioning
confidence: 80%
“…In addition, we cannot rule out the possibility that the increase in Angs could be compensatory and their action protective, since there are indications from some studies that they may reduce target organ damage in a hypertensive animal model. 27 A previous study by Sie et al 28 was the first that attempted to find a relation between arterial stiffness and angiogenic factors, and more specifically transforming growth factor. The study was not able to show any significant correlation.…”
Section: Discussionmentioning
confidence: 99%